2020
DOI: 10.26434/chemrxiv.12296261.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Protein-Coated Aryl Modified Gold Nanoparticles for Cellular Uptake Study by Osteosarcoma Cancer Cells

Abstract: We synthesized protein-coated gold nanoparticles using green and chemical reduction routes for cellular uptake study. In the current work, we coated gold-aryl nanoparticles of the type AuNPs-C<sub>6</sub>H<sub>4</sub>-4-COOH with BSA, collagen, zein and lysozyme proteins. Both routes were carried out without phase-transfer catalysts or extraneous stabilizing agents. High crystallinity of the AuNPs synthesized by the green route can be seen in the transmission electron microscopy images.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Some nanoparticles were tagged with FITC [ 8 ]. Afterwards, MG-63 cells were treated with the tagged gold nanoparticles for 24 h. Flow cytometry and confocal microscopy methods were used to confirm the uptakes of the nanoparticles [ 8 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Some nanoparticles were tagged with FITC [ 8 ]. Afterwards, MG-63 cells were treated with the tagged gold nanoparticles for 24 h. Flow cytometry and confocal microscopy methods were used to confirm the uptakes of the nanoparticles [ 8 ].…”
Section: Main Textmentioning
confidence: 99%
“…They have shown outstanding biocompatibility and unique applications in DNA stabilization, Bovine Serum Albumin (BSA) delivery, cellular uptake, lysozyme bioconjugation for antibiotic-resistant bacteria and insulin defibrillation [ 6 , 7 ]. Furthermore, our recent study also shows that these aryl-gold nanoparticles having various protein coats are easily uptaken by MG-63 cells [ 8 ]. Unlike the gold nanoparticles that are reported to have citrate shells, gold-aryl nanoparticles have aryl functional groups covalently linked through carbon to the gold core and highly water dispersible which make them ideal for cellular uptake study [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gold-carbon nanoparticles are synthesized from aryldiazonium gold(III) salts using various routes including chemical, spontaneous, electrochemical, and femtosecond laser ablation. [64][65][66][67] Two interesting routes are discussed here, namely electrochemical reduction in water in the presence of polyaniline (PANI) 64 and the femtosecond laser ablation of the salts in acetonitrile. 65 We have shown that electrochemical reduction of diazonium gold(III) salts in the presence of PANI at different potential values produce PANI-AuNPs nanocomposites.…”
Section: Preparation Of Gold-carbon Nanoparticles From Aryldiazonium Gold Salts Using Physical Methodsmentioning
confidence: 99%
“…[81][82][83] The water-soluble bioconjugates synthesized using diazonics have contributed significantly to development of nanomedicine engineering. 66,67,70,84,85 The bonding between the gold core and aryl shell appears to be robust in biological fluids. 28,66,67,85 Carboxyl-modified gold NPs were successfully implemented in the in vitro delivery of insulin and inhibition of insulin fibrillation.…”
Section: Diazonics In Nanomedicine Engineeringmentioning
confidence: 99%
See 1 more Smart Citation